2022
DOI: 10.1002/cctc.202200253
|View full text |Cite
|
Sign up to set email alerts
|

Novel Fe‐modified CeO2 Nanorod Catalyst for the Dimethyl Carbonate Formation from CO2 and Methanol

Abstract: A series of Fe-modified CeO 2 catalysts with nanoparticle, nanorod, nanocube and nano-octahedron morphologies were synthesized and applied for direct synthesis of dimethyl carbonate (DMC) from CO 2 and methanol. The Fe-modification shows a remarkably promoting effect on the formation of DMC over Fe-modified CeO 2 nanorod. The DMC yield was improved from 0.202 to 2.568 mmol DMC per g cat by 2 %Fe-modification of CeO 2 nanorod. A synergistic effect among the moderate acidbasic sites, specific surface area and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…(g) Pressure (MPa) Temp. (°C) CeO 2 Hydrothermal Spindle 0.1 5.0 140 1.38 [17] CeO 2 Precipitation Spindle 1.0 8.0 140 13.84 [43] CeO 2 Hydrothermal Rod 0.2 3.0 160 0.20 [44] CeO 2 Solvothermal Thermal reduction under H 2 Wire 0.2 5.0 120 16.85 [35] CuO/CeO 2 Hydrothermal Impregnation Rod 0.5 3.0 140 0.60 [70] CeO 2 Precipitation Spindle 0.1 4.5 140 14.44 This work CeO 2 -B Precipitation Chemical redox etching Spindle 0.1 4.5 140 17.90 This work CeO 2 -B-CuO Precipitation Chemical redox etching & Impregnation Spindle 0.1 4.5 140 16.47 This work <...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(g) Pressure (MPa) Temp. (°C) CeO 2 Hydrothermal Spindle 0.1 5.0 140 1.38 [17] CeO 2 Precipitation Spindle 1.0 8.0 140 13.84 [43] CeO 2 Hydrothermal Rod 0.2 3.0 160 0.20 [44] CeO 2 Solvothermal Thermal reduction under H 2 Wire 0.2 5.0 120 16.85 [35] CuO/CeO 2 Hydrothermal Impregnation Rod 0.5 3.0 140 0.60 [70] CeO 2 Precipitation Spindle 0.1 4.5 140 14.44 This work CeO 2 -B Precipitation Chemical redox etching Spindle 0.1 4.5 140 17.90 This work CeO 2 -B-CuO Precipitation Chemical redox etching & Impregnation Spindle 0.1 4.5 140 16.47 This work <...…”
Section: Resultsmentioning
confidence: 99%
“…However, due to thermodynamic limitations as shown, CO 2 + 2CH 3 OH → (CH 3 O) 2 CO + H 2 O (ΔG° = 26 kJ.mol −1 ), the conversion reaction requires energy input and the DMC yield is relatively low [33] , [34] , [35] . Hence, various metal oxide catalysts, for instance, K 2 CO 3 [36] , [37] , ZrO 2 [38] , [39] , TiO 2 [40] , [41] and CeO 2 [19] , [42] , [43] , [44] , have been used to increase the reaction rate and DMC formation.…”
Section: Introductionmentioning
confidence: 99%
“…The X-ray diffraction pattern (Figure S3) specified the presence of two phases in the CHP-6 materials, i. e. Ce(OH)PO 4 and CeO 2 ; because this obtained XRD pattern matches the JCPDS 96-723-2934 for orthorhombic Ce(OH)PO 4 phase and JCPDS 96-900-9009 for cubic CeO 2 . [25] This wide-angle XRD analysis evidently specifies that the as-synthesized materials are highly crystalline in nature.…”
Section: Powder Xrd and Ft-ir Analysismentioning
confidence: 94%
“…[14] Luo et al reported that CeO 2 nanoparticle performance for the synthesis of DMC from CO 2 and methanol reached up to 1.6 mmol g À1 , exceeding the activity of nanorods, nanocubes, and nano-octahedrons. [15] It was proved that the Lewis acid-base sites on the catalyst surface were intimately connected with the formation of DMC. For instances, Xie and co-workers demonstrated that controlled vacancy clusters on the CeO 2 surfaces construct Lewis acid-base pairs to effectively enhance CO 2 /CH 3 OH activation and formation of key intermediates of methoxy carbonate species for the synthesis of DMC.…”
Section: Et Al Have Demonstrated With the Model Ofmentioning
confidence: 99%